635 Validation of Virtual Reality Training for Femoral Nail Procedures in Orthopaedic Surgery: A Systematic Review. (19th August 2022) - Sharma, M; Khanal, P; Patel, N; Patel, A
Abstract: Aim: To evaluate the effectiveness and shortcomings of virtual reality (VR) simulators to teach and assess femoral nail procedures. Method: The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) algorithm was used to screen and select studies from four databases: Embase (via Ovid), PubMed, Web of Science and Scopus. In total, fifty titles were identified. Of these, four studies met the eligibility criteria and underwent narrative analyses. Results: The studies consisted of 86 participants and measured 17 outcomes associated with procedural learning. Three studies showed that VR simulation trained cognitive and psychomotor skills relevant to the real procedure (construct validity) and one study showed that these skills were transferrable to another simulation model (transfer validity). In addition, two studies employed questionnaires to investigate the visual realism (face validity) and technical accuracy (content validity) of the VR simulators, receiving positive feedback for both components. The main limitation pervading all simulators was the minimality of haptic feedback when interacting with the virtual instruments and environment. Conclusions: This systematic review demonstrates that VR simulators may be a viable tool for trainees to safely learn and practise femoral nail procedures outside the theatre. However, there remains scope for design and technological enhancements to further improve their effectiveness. To facilitate this continued development, we are presently conducting a large-scale validation study for the DePuy Synthes (Johnson and Johnson) Trochanteric Femoral Nail Advanced VR system, comprising participants from two London, UK, Hospital Trusts.